Children and Minecraft: A survey of children's digital play. (September 2018) - Mavoa, Jane; Carter, Marcus; Gibbs, Martin
Digital games such as Minecraft currently hold a position of significance in the media diets of many children. However, little is known explicitly about just who plays, with whom and how. This article presents the quantitative results of a survey of 753 parents of children aged 3–12 years about their child's engagement with Minecraft. Our results establish Minecraft as the dominant digital game title played by this age group, particularly on tablet devices. We provide evidence of a marked early gendering of children's Minecraft play and engagement with meta-game material. This research gives particular impetus to efforts aimed at ensuring gender equity in digital game–related cultural spaces inhabited by children. It also highlights the importance of collecting game-specific descriptive information, rather than limiting studies to aggregate measures of 'screen time'.